Negative electrode material, negative electrode plate, electrochemical device and preparation method of negative electrode material

By shaping natural graphite and applying multi-directional pressure, the pore orientation degree is adjusted and the amorphous carbon cladding layer is formed, the problem of instability of natural graphite structure is solved and the circulation and fast charging performance of lithium-ion batteries is improved.

CN119153635APending Publication Date: 2024-12-17ENVISION DYNAMICS TECH (JIANGSU) CO LTD +3
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310715733.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The natural graphite of existing lithium-ion batteries is structurally unstable as the negative electrode material, which affects its circulation performance and fast charging performance.

Method used

By shaping natural graphite and applying multi-directional pressure, the orientation of its particles and pores is adjusted, so that its average pore orientation is between 5° and 40°, and an amorphous carbon coating layer is formed on the surface of the particles to enhance structural stability and lithium ion transmission efficiency.

Benefits of technology

It improves the cycling performance and fast charging performance of natural graphite in electrochemical devices, ensures the structural stability of the negative electrode material and the lithium ion transmission efficiency, and improves the overall performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153635A_ABST
    Figure CN119153635A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material, a negative electrode plate, an electrochemical device and a preparation method of the negative electrode material, and belongs to the technical field of secondary batteries, the negative electrode material comprises natural graphite, and pores are formed in particles of the natural graphite; the average pore orientation degree of the natural graphite is 5-40 degrees, and the pore orientation degree is the included angle between the pore orientation and the particle orientation in the natural graphite particles. According to the negative electrode material, the negative electrode plate, the electrochemical device and the preparation method of the negative electrode material, the structural stability and the lithium ion transmission effect of the natural graphite in the negative electrode plate are improved, so that the cycle performance and the quick charge performance of the electrochemical device assembled with the negative electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode material, a negative electrode plate, an electrochemical device and a method for preparing the negative electrode material. Background Art

[0002] In today's era, lithium-ion secondary batteries are widely used in digital, power, and energy storage fields due to their high energy density, long cycle life, fast charging capability, low cost, and environmental protection. With the gradual increase in market share, the market has put forward higher requirements for lithium-ion batteries, such as higher energy density, longer cycle performance, and shorter fast charging time. Generally speaking, energy density, cycle performance, and fast charging performance cannot be fully achieved at the same time, so how to improve the cycle and fast charging performance of lithium-ion batteries while taking into account energy density has become one of the key research directions in the field of lithium-ion batteries.

[0003] At present, the negative electrode materials of commercial lithium-ion batteries are mainly graphite materials. Graphite materials have higher gram capacity and lower voltage platform, and have better fast charging performance. Graphite materials can be further divided into artificial graphite and natural graphite. Artificial graphite has better cycle performance and high temperature performance. Natural graphite has higher gram capacity, better processing performance and lower cost than artificial graphite. However, due to the large number of pores inside natural graphite, its cycle and high temperature performance are worse than artificial graphite without high temperature graphitization.

[0004] Therefore, it is necessary to design a negative electrode material, a negative electrode plate, an electrochemical device and a method for preparing the negative electrode material, adjust the void structure inside the natural graphite, so as to improve the cycle performance and fast charging performance of the natural graphite as a negative electrode material in the electrochemical device, thereby solving the above problems. Summary of the invention

[0005] In view of the above shortcomings of the prior art, the present invention provides a negative electrode material, a negative electrode plate, an electrochemical device and a method for preparing the negative electrode material, so as to solve the technical problem that the natural graphite is structurally unstable as a negative electrode material, which affects the cycle performance and fast charging performance of the electrochemical device.

[0006] To achieve the above object and other related objects, the present invention provides a negative electrode material, which includes: natural graphite.

[0007] The natural graphite particles have pores; the average pore orientation of the natural graphite is 5° to 40°, and the pore orientation is the angle between the pore orientation and the particle orientation in the natural graphite particles.

[0008] In an example of the present invention, the negative electrode material includes a core body and a coating layer, the core body includes the natural graphite, and the coating layer includes amorphous carbon.

[0009] In one example of the present invention, the average particle size of the natural graphite particles is 5 to 20 μm.

[0010] On the other hand, the present invention provides a method for preparing the negative electrode material described in any of the above examples, and the preparation method comprises the following steps: shaping a natural graphite raw material to obtain a first graphite precursor; applying a pressure P1 to the first graphite precursor along a first direction, and after holding the pressure for a time T1, maintaining the pressure P1 unchanged and applying a pressure P2 to the first graphite precursor along a second direction, and after holding the pressure for a time T2, obtaining a second graphite precursor; mixing the second graphite precursor with a coating agent and performing a carbon coating treatment to obtain a negative electrode material; wherein the first direction is perpendicular to the second direction, and the pressure P1 is less than the pressure P2.

[0011] In one example of the present invention, the natural graphite raw material includes at least one of flake graphite and microcrystalline graphite.

[0012] In one example of the present invention, the shaping process of the natural graphite raw material includes: crushing, spheroidizing and classifying the natural graphite raw material to obtain the first graphite precursor; wherein the average particle size of the first graphite precursor is 10 to 20 μm.

[0013] In an example of the present invention, the pressure of the pressure P1 is 5-10 MPa, the time T1 is 0.5-1 hour, the pressure of the pressure P2 is 10-20 MPa, and the time T2 is 1-2 hours.

[0014] In one example of the present invention, the coating agent includes at least one of coal tar, petroleum asphalt, medium-temperature asphalt, phenolic resin and ethylene tar.

[0015] In one example of the present invention, the mass ratio of the second graphite precursor to the coating agent is (5-20):1, and the carbon coating treatment temperature of the second graphite precursor and the coating agent is 1000-1200°C.

[0016] The present invention also provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, and the negative electrode active material layer includes the negative electrode material described in any one of the above examples.

[0017] In one example of the present invention, the average pore orientation degree of the pores in the negative electrode material relative to the plane of the negative electrode current collector is 5° to 40°.

[0018] The present invention also provides an electrochemical device, which includes a positive electrode plate, a separator, an electrolyte, and a negative electrode plate as described in any one of the above examples.

[0019] The present invention adjusts the orientation of the pores in the natural graphite particles to 5° to 40° relative to the particles. After the natural graphite is rolled on the negative electrode current collector as a negative electrode material, the orientation of the natural graphite particles tends to be parallel to the surface direction of the negative electrode current collector, while the orientation of the pores inside the particles tends to be perpendicular to the surface of the negative electrode current collector. The pore structure in the natural graphite that tends to be perpendicular to the surface of the negative electrode current collector can form a large number of lithium ion channels with low tortuosity in the negative electrode active material layer, improve the wetting effect of the pores of the negative electrode material in the electrolyte, improve the lithium ion transmission efficiency between the negative electrode material and the electrolyte and even the fast charging capacity of the overall negative electrode plate. At the same time, the pore structure can also help the natural graphite to be structurally oriented on the negative electrode plate, improve the structural stability of the natural graphite on the negative electrode plate, and ensure that the negative electrode material is not easily deformed and has good cycle performance.

[0020] The negative electrode material of the present invention improves the structural stability and lithium ion transmission effect of natural graphite, thereby improving the cycle performance and fast charging performance of the electrochemical device equipped with the negative electrode material. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 It is a scanning electron microscope schematic diagram of natural graphite in the prior art;

[0023] Figure 2 A scanning electron microscope schematic diagram of a negative electrode material in one embodiment of the present invention;

[0024] Figure 3 Schematic diagram of a process for preparing a negative electrode material in one embodiment of the present invention.

[0025] Component number description

[0026] A. Particle orientation line; B. Pore orientation line. DETAILED DESCRIPTION

[0027] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0028] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.

[0029] In this specification, the average particle size (D50) may be defined as the particle size corresponding to 50% of the volume accumulation in the particle size distribution curve of the particles. The average particle size (D50) may be measured, for example, by a laser diffraction method. The laser diffraction method is generally capable of measuring particle sizes ranging from the submicron range to several millimeters, thereby obtaining results with high reproducibility and high resolution.

[0030] In this specification, the pore orientation of natural graphite is the angle between the pore orientation line in the particle and the particle orientation line, and the average pore orientation is the average value of the pore orientation of at least 100 particles. In the cross section analysis of a graphite particle, the line connecting the two points with the longest straight-line distance on the outer edge of the pore inside the particle cross section is defined as pore orientation line B, and the line connecting the two points with the longest straight-line distance on the outer edge of the particle is defined as particle orientation line A.

[0031] The present invention provides a negative electrode material, which is used to make a negative electrode plate of an electrochemical device. An electrochemical device generally includes a positive electrode material, a negative electrode material, an electrolyte, a diaphragm, and corresponding connecting accessories and circuits. The positive and negative electrode materials can deintercalate lithium ions to achieve energy storage and release, the electrolyte is a carrier for lithium ions to be transmitted between the positive and negative electrodes, and the diaphragm can pass lithium ions but is not conductive, thereby separating the positive and negative electrodes to prevent short circuits. The positive and negative electrode materials generally play a decisive role in key performance factors such as the energy storage function of a lithium battery, the energy density of its battery cell, cycle performance, and safety.

[0032] like Figure 1As shown, natural graphite has higher gram capacity, better processing performance and lower cost than artificial graphite. However, the average pore orientation of a large number of pores in natural graphite is below 5°, and the structural stability and electrolyte wetting effect of natural graphite on the negative electrode sheet cannot be improved after processing on the current collector. Among them, due to the soft texture of natural graphite, its internal pores and particle orientation tend to be in the same direction. Therefore, when natural graphite is used as a negative electrode material and rolled on the negative electrode current collector, the particle orientation and pore orientation of natural graphite tend to be parallel to the surface of the negative electrode current collector at the same time, and the pore structure parallel to the current collector surface in the negative electrode active material layer has a high tortuosity and a complex orientation structure, which can neither help the natural graphite to stabilize the structure on the negative electrode current collector and ensure the long-term cycle performance of natural graphite, nor can it form vertical lithium ion channels distributed along the surface of the negative electrode current collector in the layer to help improve the lithium ion transmission efficiency of natural graphite and even the overall fast charging ability of the negative electrode.

[0033] To solve the structural defects of natural graphite, such as Figure 2 As shown, the present invention provides a negative electrode material, which includes natural graphite, and the particles of natural graphite have a pore structure. The average pore orientation of the natural graphite is 5° to 40°. For example, the average pore orientation of the natural graphite can be 5°, 6°, 8°, 9°, 10°, 15°, 20°, 25°, 30°, 32°, 35° or 40°. The pore orientation is the angle between the pore orientation and the particle orientation in the natural graphite particles (that is, the angle between the pore orientation line B and the particle orientation line A).

[0034] After the above-mentioned natural graphite is rolled as a negative electrode material on the negative electrode current collector, its particle orientation is parallel to the current collector surface, and the pore orientation in the particle tends to be perpendicular to the current collector surface. In the negative electrode sheet, the pore structure in the natural graphite particles perpendicular to the current collector surface can improve the structural stability of the natural graphite on the negative electrode current collector, making the natural graphite less likely to deform and have better cycle performance. At the same time, it can also construct a vertical lithium ion channel distributed along the surface of the negative electrode current collector in the negative electrode active material layer to improve the infiltration effect of the electrolyte in the pores, improve the lithium ion transmission efficiency between the natural graphite and the electrolyte, and thus improve the overall fast charging capability of the negative electrode.

[0035] It should be noted that the material type of natural graphite in the present invention is not limited, and natural graphite includes at least one of flake graphite and microcrystalline graphite. That is, natural graphite can be flake graphite or microcrystalline graphite, or a combination of flake graphite and microcrystalline graphite. In the combination, the ratio of flake graphite and microcrystalline graphite is not limited, and they can be mixed in any ratio.

[0036] In some embodiments, the average pore orientation of natural graphite is preferably 10° to 32°, for example, 10°, 25° or 32°. In this embodiment, the secondary battery prepared by using natural graphite material as the negative electrode material has a rate retention rate of more than 80% and a cycle capacity retention rate of more than 94%.

[0037] In some embodiments, the negative electrode material includes a core body and a coating layer, wherein the core body includes natural graphite, and the core body can exist in the form of natural graphite particles, and the coating layer is coated on the surface of the core body, and the coating layer includes amorphous carbon.

[0038] The amorphous carbon can be formed by carbonizing an organic carbon source, for example, the organic carbon source can be selected from polymers such as coal tar, petroleum tar, resin and other polymer materials.

[0039] Amorphous carbon has a disordered structure and a high interlayer spacing. Therefore, using amorphous carbon as the coating material of the core can make the active ions diffuse faster in the negative electrode material particles, thereby improving the fast charging ability of the negative electrode material. At the same time, amorphous carbon can also protect the core material, greatly reducing the graphite layer peeling caused by the co-embedding of the core material due to solvent, making the negative electrode material have a higher structural stability, thereby ensuring a higher capacity and cycle life of the negative electrode material in the pole piece.

[0040] In some embodiments, in the negative electrode material of the present invention, the average particle size of the natural graphite particles is 5 to 20 μm, wherein the average particle size of the natural graphite particles can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm or 20 μm.

[0041] See also Figure 3 The present invention provides a method for preparing the negative electrode material described in any one of the above embodiments, comprising the following steps:

[0042] S1. Performing shaping treatment on natural graphite raw materials to obtain a first graphite precursor.

[0043] S2, applying a pressure P1 to the first graphite precursor along a first direction, and after holding the pressure for a time T1, maintaining the pressure P1 unchanged and applying a pressure P2 to the first graphite precursor along a second direction, and after holding the pressure for a time T2, obtaining a second graphite precursor;

[0044] Among them, the first direction is perpendicular to the second direction, and the pressure P1 is less than the pressure P2; when only a small pressure P1 is applied, the first graphite precursor particles are oriented in the vertical direction of the pressure P1, and the average pore orientation degree in the first graphite precursor is less than 5°; subsequently, when the pressures P1 and P2 are applied simultaneously, the particle orientation of the first graphite precursor is changed by pressure, while the pore orientation in the particles does not change much. Therefore, after the pressure treatment in step S2, the pore orientation degree in the first graphite precursor is larger than that of conventional natural graphite, and this natural graphite has better fast charging performance and cycle performance.

[0045] S3, mixing the second graphite precursor with a coating agent and performing carbon coating treatment to obtain a negative electrode material.

[0046] In some embodiments, step S1 includes crushing, spheroidizing and classifying the natural graphite raw material to obtain the first graphite precursor.

[0047] In step S1, the natural graphite raw material can be crushed using equipment and methods known in the art, such as air flow mill, mechanical mill or roller mill. In the crushing process, more small particles are often produced, and sometimes there are too large particles. Therefore, after crushing, classification treatment can be carried out according to demand to remove the small particles and too large particles in the crushed powder. After classification treatment, a pulverized natural graphite raw material with a good particle size distribution can be obtained. Classification treatment can be carried out using equipment and methods known in the art, such as a grading screen, a gravity classifier, a centrifugal classifier, etc.

[0048] In step S1, the edges and corners of the natural graphite raw material are polished by spherical shaping. The greater the shaping degree, the closer the particles are to spherical, which can increase the ratio of the end face to the base face. In step S1, the natural graphite raw material can be shaped by equipment and methods known in the art, such as a shaping machine or other shaping equipment.

[0049] After the natural graphite raw material is spheroidized, it is necessary to further classify the natural graphite raw material to obtain a first graphite precursor with an average particle size of 10 to 20 μm.

[0050] In step S1, the classification process can be performed using equipment and methods known in the art, such as a classification screen, a gravity classifier, a centrifugal classifier, etc.

[0051] In some embodiments, in step S1, the natural graphite raw material is selected from at least one of flake graphite and microcrystalline graphite. That is, the natural graphite raw material can be flake graphite or microcrystalline graphite, or a combination of flake graphite and microcrystalline graphite. In the combination, the ratio of flake graphite and microcrystalline graphite is not limited, and they can be mixed in any proportion.

[0052] In some embodiments, in step S2, the first graphite precursor is placed in a pressurizing device, and the pressurizing device is driven to apply a pressure P1 of 5 to 10 MPa to the first graphite precursor in a first direction, such as pressure P1 can be 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa or 10 MPa, and the holding time T1 is 0.5 to 1 hour, such as 0.5, 0.6, 0.8, 0.9 or 1 hour; and then, under the premise of maintaining the pressure P1 unchanged, a pressure P2 of 10 to 20 MPa is applied to the first graphite precursor along the second direction, such as pressure P1 can be 10 MPa, 12 MPa, 15 MPa, 18 MPa or 20 MPa, and the holding time T2 is 1 to 2 hours, such as 1, 1.2, 1.5, 1.7 or 2 hours, to obtain a second graphite precursor with an average pore orientation of 5° to 40°.

[0053] It should be noted that in step S2, the specific directions of the first direction of applying pressure P1 and the second direction of applying pressure P2 are not limited, and it is only necessary to maintain the perpendicular relationship between the first direction and the second direction. In some embodiments, in step S2, the first direction of applying pressure P1 is a horizontal direction, and the second direction of applying pressure P2 is a vertical direction.

[0054] In some embodiments, step S3 includes uniformly mixing the second graphite precursor and the coating agent in a mass ratio of (5 to 20): 1, preferably in a ratio of (8 to 18): 1, so that the coating agent is coated on at least a portion of the surface of the second graphite precursor particles, and then placing the mixed second graphite precursor and coating agent at a high temperature of 1000°C to 1200°C for carbon coating treatment, so that an amorphous carbon coating layer is formed on the surface of the natural graphite, and natural graphite with an average particle size of 5 to 20 μm is obtained.

[0055] In some embodiments, in step S3, the coating agent is selected from at least one of coal tar, petroleum tar, phenolic resin and ethylene tar. Preferably, the coating agent includes at least coal tar.

[0056] The present invention further provides a negative electrode plate, which comprises a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode material of the present invention.

[0057] Among them, in the negative electrode active material layer, the average pore orientation degree of the pores in the natural graphite particles relative to the surface of the negative electrode current collector is 5° to 40°, that is, in the same cross section, the angle of the pore orientation line of the pores in the natural graphite particles relative to the surface of the negative electrode current collector.

[0058] The preparation process of the negative electrode sheet is as follows: the negative electrode material, conductive carbon black (Super P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are mixed at a mass ratio of 97:1:1:1, deionized water is added, the solid content of the slurry is adjusted to 55%, and the mixture is fully stirred to obtain a negative electrode slurry, and the negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil, and the negative electrode sheet is prepared through drying, cold pressing, slitting and other processes. Among them, the conductive agent can also be selected from: at least one of acetylene black, carbon nanotubes, graphene, VGCF and other conductive materials; the binder can also be selected from: at least one of PVDF, PTFE and the like.

[0059] The present invention also provides an electrochemical device, the electrochemical device includes the negative electrode sheet of the present invention, the electrochemical device is such as a lithium ion battery, the battery includes a positive electrode sheet, a negative electrode sheet, a separator disposed between the positive electrode sheet and the negative electrode sheet, and an electrolyte. Among them, the positive and negative electrode materials can deintercalate lithium ions to achieve energy storage and release, the electrolyte is a carrier for lithium ions to be transmitted between the positive and negative electrodes, and the separator can pass lithium ions but is not conductive, thereby separating the positive and negative electrodes to prevent short circuits.

[0060] Preparation of positive electrode sheet: The ternary positive electrode material (LiNi 0.5 Co 0.2 Mn 0.3 O2), conductive carbon black (Super P), carbon nanotubes (CNT), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1:1:1, and a solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred and mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is prepared through drying, cold pressing, slitting and other processes. Among them, the conductive agent can also be selected from: at least one of acetylene black, carbon nanotubes, graphene, VGCF and other conductive materials; the binder can also be selected from: at least one of PVDF, PTFE and the like.

[0061] The negative electrode sheet preparation process is as mentioned above.

[0062] Preparation of diaphragm: The diaphragm is a 9μm polyethylene diaphragm coated on both sides with a ceramic coating with a thickness of 2μm.

[0063] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are uniformly mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0064] Assemble the battery: stack the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then wrap it with aluminum plastic film, inject the above-prepared electrolyte after drying, and finally prepare a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah after packaging, standing, and formation.

[0065] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.

[0066] Example 1

[0067] This embodiment provides a negative electrode material, which includes natural graphite coated with coal tar pitch, and the average pore orientation of the natural graphite is 25°. The preparation method of the negative electrode material is as follows:

[0068] S1. Crushing, spheroidizing and classifying a flake graphite raw material having an average particle size of 5 μm to obtain a first graphite precursor having an average particle size of 10 μm;

[0069] S2, placing the first graphite precursor in a pressurizing device, applying a pressure P1 of 8 MPa to the spherical first graphite precursor along a first horizontal direction, and maintaining the pressure for a time T1 to 0.5 hours; then, keeping the pressure P1 in the first direction unchanged, and continuing to apply a pressure P2 of 15 MPa to the spherical first graphite precursor along a second vertical direction, and maintaining the pressure P1 and the pressure P2 for a time T2 to 1.5 hours, to obtain a second graphite precursor with an average particle size of 8 μm;

[0070] S3. Mix the second graphite precursor and the coating agent in a mass ratio of 10:1, and place them at a temperature of 1150° C. for heat coating and carbonization to obtain a negative electrode material with an average particle size of 8 μm; wherein the coating agent is coal tar.

[0071] This embodiment also uses the above negative electrode material to prepare a secondary lithium battery, and the preparation method of the secondary lithium battery is as follows:

[0072] (1) Preparation of positive electrode sheet:

[0073] The ternary positive electrode material (LiNi 0.5 Co 0.2 Mn 0.3O2), conductive carbon black (Super P), carbon nanotubes (CNT), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1:1:1, and solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred thoroughly to obtain a positive electrode slurry; the mixture is stirred under the action of a vacuum mixer until the system is uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on a 16μm aluminum foil current collector, and then the aluminum foil current collector is dried at room temperature and transferred to an oven at 80℃~120℃ for 6h, and then cold pressed and cut to obtain a positive electrode sheet.

[0074] (2) Preparation of negative electrode sheet:

[0075] The negative electrode material, conductive carbon black (Super P), thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed in a mass ratio of 97:1:1:1, and deionized water is added to adjust the solid content of the slurry to 55%, and then the mixture is fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both sides of an 8μm negative electrode current collector copper foil; after drying at room temperature, it is transferred to an oven for drying, and then cold pressed, slitting and other processes are performed to obtain a negative electrode sheet.

[0076] (3) Preparation of electrolyte:

[0077] In an argon atmosphere glove box with a water content of <10ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are uniformly mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0078] (4) Diaphragm preparation:

[0079] The diaphragm is a 9μm polyethylene diaphragm coated on both sides with a ceramic coating with a thickness of 2μm.

[0080] (5) Assembling the battery:

[0081] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then, they are wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, and sealed after injecting 3.0g / Ah of electrolyte. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah is finally prepared.

[0082] The specific steps and conditions for electrolyte formation are as follows: after the electrolyte is injected, maintain a hot pressure environment of 0.1MPa, charge at 0.02C for 17min at 45°C in a static state, stand for 5min and then charge to 0.3Ah at 0.02C, then cut off the air bag and vacuum seal, and stand at room temperature for 48h to complete the electrolyte formation.

[0083] Example 2: Please refer to Table 1

[0084] This embodiment provides a natural graphite with an average particle size of 15 μm, a coating agent of medium-temperature asphalt, and an average pore orientation of 32° as a negative electrode material. The preparation process of the negative electrode material is as follows:

[0085] S1. Crushing, spheroidizing and classifying a flake graphite raw material having an average particle size of 10 μm to obtain a first graphite precursor having an average particle size of 20 μm;

[0086] S2, placing the first graphite precursor in a pressurizing device, applying a pressure P1 of 6 MPa to the spherical first graphite precursor along a first horizontal direction, and maintaining the pressure for a time T1 to 0.6 hours; then, keeping the pressure P1 in the first direction unchanged, and continuing to apply a pressure P2 of 18 MPa to the spherical first graphite precursor along a second vertical direction, and maintaining the pressure P1 and the pressure P2 for a time T2 to 1.2 hours, to obtain a second graphite precursor with an average particle size of 15 μm;

[0087] S3. Mix the second graphite precursor and the coating agent in a mass ratio of 15:1, and place them at a temperature of 1100°C for heat coating and carbonization to obtain a negative electrode material with an average particle size of 15 μm; wherein the coating agent is medium-temperature asphalt.

[0088] Example 3: Please refer to Table 1

[0089] This embodiment provides a natural graphite with an average particle size of 18 μm, a coating agent of phenolic resin, and an average pore orientation of 10° as a negative electrode material. The preparation process of the negative electrode material is as follows:

[0090] S1. Crushing, spheroidizing and classifying a flake graphite raw material having an average particle size of 15 μm to obtain a first graphite precursor having an average particle size of 25 μm;

[0091] S2, placing the first graphite precursor in a pressurizing device, applying a pressure P1 of 9 MPa to the spherical first graphite precursor along a first horizontal direction, and maintaining the pressure for a time T1 to 0.9 hours; then, keeping the pressure P1 in the first direction unchanged, and continuing to apply a pressure P2 of 12 MPa to the spherical first graphite precursor along a second vertical direction, and maintaining the pressure P1 and the pressure P2 for a time T2 to 1 hour, to obtain a second graphite precursor with an average particle size of 18 μm;

[0092] S3. Mix the second graphite precursor and the coating agent in a mass ratio of 8:1, and place them at a temperature of 1050°C for heat coating and carbonization to obtain a negative electrode material with an average particle size of 18 μm; wherein the coating agent is phenolic resin.

[0093] Example 4: Please refer to Table 1

[0094] This embodiment provides a natural graphite with an average particle size of 20 μm, a coating agent of coal tar pitch, and an average pore orientation of 5° as a negative electrode material. The preparation process of the negative electrode material is as follows:

[0095] S1. Crushing, spheroidizing and classifying a flake graphite raw material having an average particle size of 5 μm to obtain a first graphite precursor having an average particle size of 25 μm;

[0096] S2, placing the first graphite precursor in a pressurizing device, applying a pressure P1 of 5 MPa to the spherical first graphite precursor along a first horizontal direction, and maintaining the pressure for a time T1 to 0.5 hours; then, keeping the pressure P1 in the first direction unchanged, and continuing to apply a pressure P2 of 20 MPa to the spherical first graphite precursor along a second vertical direction, and maintaining the pressure P1 and the pressure P2 for a time T2 to 2 hours, to obtain a second graphite precursor with an average particle size of 20 μm;

[0097] S3. Mix the second graphite precursor and the coating agent in a mass ratio of 20:1, and place them at a temperature of 1200° C. for heat coating and carbonization to obtain a negative electrode material with an average particle size of 20 μm; wherein the coating agent is coal tar.

[0098] Example 5: Please refer to Table 1

[0099] This embodiment provides a natural graphite with an average particle size of 5 μm, a coating agent of coal tar pitch, and an average pore orientation of 40° as a negative electrode material. The preparation process of the negative electrode material is as follows:

[0100] S1. Crushing, spheroidizing and classifying a flake graphite raw material having an average particle size of 2 μm to obtain a first graphite precursor having an average particle size of 10 μm;

[0101] S2, placing the first graphite precursor in a pressurizing device, applying a pressure P1 of 10 MPa to the spherical first graphite precursor along a first horizontal direction, and maintaining the pressure for a time T1 to 1 hour; then, keeping the pressure P1 in the first direction unchanged, and continuing to apply a pressure P2 of 20 MPa to the spherical first graphite precursor along a second vertical direction, and maintaining the pressure P1 and the pressure P2 for a time T2 to 2 hours, to obtain a second graphite precursor with an average particle size of 5 μm;

[0102] S3. Mix the second graphite precursor and the coating agent in a mass ratio of 5:1, and place them at a temperature of 1000°C for heat coating and carbonization to obtain a negative electrode material with an average particle size of 5 μm; wherein the coating agent is coal tar.

[0103] Example 6: Please refer to Table 1

[0104] This embodiment provides a natural graphite with an average particle size of 7 μm, a coating agent of coal tar pitch, and an average pore orientation of 6° as a negative electrode material. The difference between the preparation process of the negative electrode material in this embodiment and that in embodiment 1 is as follows:

[0105] In step S2, a pressure P1 of 4 MPa is applied to the spherical first graphite precursor along a first horizontal direction, and the pressure is maintained for a time T1 to 0.4 hours; then, the pressure P1 in the first direction is kept unchanged, and a pressure P2 of 15 MPa is continuously applied to the spherical first graphite precursor along a second vertical direction. After the pressures P1 and P2 are simultaneously applied for a time T2 to 1.5 hours, a second graphite precursor with an average particle size of 7 μm is obtained.

[0106] Example 7: Please refer to Table 1

[0107] This embodiment provides a natural graphite with an average particle size of 6 μm, a coating agent of coal tar pitch, and an average pore orientation of 8° as a negative electrode material. The difference between the preparation process of the negative electrode material in this embodiment and that in Example 1 is as follows:

[0108] In step S2, a pressure P1 of 12 MPa is applied to the spherical first graphite precursor along a first horizontal direction, and the pressure is maintained for a time period of T1 to 1.5 hours; then, the pressure P1 in the first direction is kept unchanged, and a pressure P2 of 15 MPa is continuously applied to the spherical first graphite precursor along a second vertical direction. After the pressures P1 and P2 are simultaneously applied for a time period of T2 to 1.5 hours, a second graphite precursor with an average particle size of 6 μm is obtained.

[0109] Example 8: Please refer to Table 1

[0110] This embodiment provides a natural graphite with an average particle size of 6 μm, a coating agent of coal tar pitch, and an average pore orientation of 9° as a negative electrode material. The difference between the preparation process of the negative electrode material in this embodiment and that in Example 1 is as follows:

[0111] In step S2, a pressure P1 of 8 MPa is applied to the spherical first graphite precursor along a first horizontal direction, and the pressure is maintained for a time T1 to 0.8 hours; then, the pressure P1 in the first direction is kept unchanged, and a pressure P2 of 22 MPa is applied to the spherical first graphite precursor along a second vertical direction. After the pressures P1 and P2 are simultaneously applied for a time T2 to 2.1 hours, a second graphite precursor with an average particle size of 6 μm is obtained.

[0112] Example 9: Please refer to Table 1

[0113] This embodiment provides a natural graphite with an average particle size of 8 μm, a coating agent of coal tar pitch, and an average pore orientation of 6° as a negative electrode material. The difference between the preparation process of the negative electrode material in this embodiment and that in Example 1 is as follows:

[0114] In step S2, a pressure P1 of 8 MPa is applied to the spherical first graphite precursor along a first horizontal direction, and the pressure is maintained for a time period of T1 to 0.8 hours. Then, the pressure P1 in the first direction is kept unchanged, and a pressure P2 of 9 MPa is applied to the spherical first graphite precursor along a second vertical direction. After the pressures P1 and P2 are simultaneously applied for a time period of T2 to 0.9 hours, a second graphite precursor with an average particle size of 8 μm is obtained.

[0115] Example 10: Please refer to Table 1

[0116] This embodiment provides a natural graphite with an average particle size of 12 μm, a coating agent of coal tar pitch, and an average pore orientation of 3° as a negative electrode material. The preparation process of the negative electrode material is as follows:

[0117] S1. Crushing, spheroidizing and classifying a flake graphite raw material having an average particle size of 10 μm to obtain a first graphite precursor having an average particle size of 15 μm;

[0118] S2, placing the first graphite precursor in a pressurizing device, applying a pressure P1 of 10 MPa to the spherical first graphite precursor along a first horizontal direction, and maintaining the pressure for a time T1 to 0.6 hours; then, keeping the pressure P1 in the first direction unchanged, and continuing to apply a pressure P2 of 10 MPa to the spherical first graphite precursor along a second vertical direction, and maintaining the pressure P1 and the pressure P2 for a time T2 to 1.2 hours, to obtain a second graphite precursor with an average particle size of 12 μm;

[0119] S3. Mix the second graphite precursor and the coating agent in a mass ratio of 10:1, and place them at a temperature of 1150° C. for heat coating and carbonization to obtain a negative electrode material with an average particle size of 12 μm; wherein the coating agent is coal tar.

[0120] Example 11: Please refer to Table 1

[0121] This embodiment provides a natural graphite with an average particle size of 9 μm, a coating agent of coal tar pitch, and an average pore orientation of 45° as a negative electrode material. The preparation process of the negative electrode material is as follows:

[0122] S1. Crushing, spheroidizing and classifying a flake graphite raw material having an average particle size of 8 μm to obtain a first graphite precursor having an average particle size of 12 μm;

[0123] S2, placing the first graphite precursor in a pressurizing device, applying a pressure P1 of 5 MPa to the spherical first graphite precursor along a first horizontal direction, and maintaining the pressure for a time T1 to 1 hour; then, keeping the pressure P1 in the first direction unchanged, and continuing to apply a pressure P2 of 20 MPa to the spherical first graphite precursor along a second vertical direction, and maintaining the pressure P1 and the pressure P2 for a time T2 to 2 hours, to obtain a second graphite precursor with an average particle size of 9 μm;

[0124] S3. Mix the second graphite precursor and the coating agent in a mass ratio of 10:1, and place them at a temperature of 1150° C. for heat coating and carbonization to obtain a negative electrode material with an average particle size of 9 μm; wherein the coating agent is coal tar.

[0125] Comparative Example 1: Please refer to Table 1

[0126] This embodiment provides a natural graphite with an average particle size of 8 μm, a coating agent of coal tar pitch, and an average pore orientation of 5° as a negative electrode material. The difference between the preparation process of the negative electrode material in this embodiment and that in embodiment 1 is as follows:

[0127] In step S2, a pressure P1 of 15 MPa is applied to the spherical first graphite precursor along a first horizontal direction, and the pressure is maintained for a time T1 to 1.5 hours; then, the pressure P1 in the first direction is kept unchanged, and a pressure P2 of 8 MPa is applied to the spherical first graphite precursor along a second vertical direction. After the pressures P1 and P2 are simultaneously applied for a time T2 to 0.8 hours, a second graphite precursor with an average particle size of 8 μm is obtained.

[0128] Comparative Example 2: Please refer to Table 1

[0129] This embodiment provides a natural graphite with an average particle size of 9 μm, a coating agent of coal tar pitch, and an average pore orientation of 4° as a negative electrode material. The difference between the preparation process of the negative electrode material in this embodiment and that in embodiment 1 is as follows:

[0130] In step S2, only a horizontal pressure P1 of 8 MPa is applied to the first graphite precursor, and the pressure is maintained for a time T1 to 0.8 hours, while the vertical pressure P2 is not continuously applied to the first graphite precursor.

[0131] Comparative Example 3: Please refer to Table 1

[0132] This embodiment provides a natural graphite with an average particle size of 8 μm, a coating agent of coal tar pitch, and an average pore orientation of 5° as a negative electrode material. The difference between the preparation process of the negative electrode material in this embodiment and that in embodiment 1 is as follows:

[0133] In step S2, only a horizontal pressure P1 of 15 MPa is applied to the first graphite precursor for a holding time T1 to 1.5 hours, and the vertical pressure P2 is not applied to the first graphite precursor.

[0134] Comparative Example 4: Please refer to Table 1

[0135] This embodiment provides a natural graphite with an average particle size of 10 μm, a coating agent of coal tar pitch, and an average pore orientation of 3° as a negative electrode material. The preparation process of the negative electrode material in this embodiment is different from that in Example 1 in that:

[0136] In step S2, no pressure is applied to the first graphite precursor.

[0137] Lithium batteries containing negative electrode materials prepared in Examples 1 to 11 and Comparative Examples 1 to 4 were subjected to average pore orientation test, average particle size test, cycle capacity retention test and rate retention test to verify the improvement effect of the negative electrode materials in different embodiments on the cycle performance and fast charging cycle performance of the electrochemical device.

[0138] Average particle size tests include:

[0139] 50 mg of graphite was placed in a small beaker, 5 drops of 1% ethylphenyl polyethylene glycol aqueous solution were added, and then 20 mL of deionized water was added to disperse the graphite. The particle size volume distribution was tested using a laser particle size analyzer. The particle refractive index was 2.68, the solvent refractive index was 1.33, and the light shielding was 5-10%. The particle size that accounts for 50% of the volume particle size distribution from small to large is the average particle size of the material.

[0140] Average pore orientation tests include:

[0141] The negative electrode sheet was polished by argon ion beam, and the cross section was observed under a scanning electron microscope with a magnification of 2000 times. The interior of a natural graphite particle cross section was analyzed, and the line between the two points with the longest straight-line distance on the outer edge of a graphite particle cross section was defined as the particle orientation line, and the line between the two points with the longest straight-line distance on the outer edge of the pore inside the particle cross section was defined as the pore orientation line. The angle between the longest pore orientation line in a particle and the particle orientation line was defined as the pore orientation degree of the particle. The average value calculated by counting 100 particles was the average pore orientation degree.

[0142] Cyclic capacity retention test includes:

[0143] At 25℃, charge to 4.35V at 1C rate and constant current and voltage (constant voltage cutoff current is 0.05C), then discharge to 2.8V at 1C rate and constant current. This is one cycle. Repeat this process for 200 cycles. The ratio of the discharge capacity at the 200th cycle to the discharge capacity at the 1st cycle is the cycle capacity retention rate.

[0144] The rate retention test includes:

[0145] At a constant temperature of 25°C, charge the battery to 4.35V at a constant current and voltage of 0.33C (the cut-off current of the constant voltage is 0.05C), and then discharge it to 2.8V at a constant current of 0.33C to obtain a 0.33C capacity. Charge the battery to 4.35V at a constant current and voltage of 0.33C (the cut-off current of the constant voltage is 0.05C), and then discharge it to 2.8V at a constant current of 2C to obtain a 2C capacity. The ratio of the 2C capacity to the 0.33C capacity is the rate retention rate.

[0146] The preparation parameters of the negative electrode materials in Examples 1 to 11 and Comparative Examples 1 to 4 are shown in Table 1, and the test result parameters of the negative electrode materials in lithium batteries are shown in Table 2.

[0147] Table 1: Preparation parameters of negative electrode materials in Examples 1 to 14 and Comparative Examples 1 to 3

[0148]

[0149]

[0150] Table 2: Test results of cycle capacity retention and rate retention of lithium batteries prepared from negative electrode materials in Examples 1 to 14 and Comparative Examples 1 to 3

[0151]

[0152]

[0153] From the preparation parameters and test results of the negative electrode materials in Examples 1 to 5 and Comparative Example 4, it can be seen that the preparation method of the present invention can effectively adjust the orientation of the pores in natural graphite relative to the particles, so that the average pore orientation degree is adjusted from less than 5° to 5° to 40°.

[0154] From the test results, it can be seen that compared with natural graphite without orientation adjustment, natural graphite with an average pore orientation of 5° to 40° as the negative electrode material can improve the cycle performance and fast charging performance of the lithium battery, so that the cycle capacity retention rate and rate retention rate of the lithium battery are maintained at more than 93% and 80%, respectively. Among them, natural graphite with an average pore orientation of 10° to 32° is preferred as the negative electrode material, which can further improve the cycle capacity retention rate and rate retention rate of the battery assembled with the negative electrode material, so that the cycle capacity retention rate and rate retention rate are maintained at about 95% and 82%.

[0155] It can be seen from the preparation parameters and test results of the negative electrode materials in Example 1 and Comparative Examples 1 to 3 that, on the basis of applying a smaller pressure P1 along the pore orientation, a larger pressure P2 is applied to the natural graphite along the particle orientation to adjust the pore orientation relative to the particle in the natural graphite particles.

[0156] In Comparative Example 1, a relatively large pore orientation pressure P1 is first applied to the natural graphite, so that the subsequent particle orientation pressure P2 cannot adjust the particle orientation of the natural graphite, resulting in a low average pore orientation. In Comparative Examples 2 and 3, pressure P1 is only applied to the natural graphite along the pore orientation, and the relative orientation of the pores and particles in the natural graphite cannot be adjusted.

[0157] From the test results, it can be seen that when the natural graphite with lower average porosity in Comparative Examples 1 to 4 is used as the negative electrode material, the cycle capacity retention rate and rate retention rate of the lithium battery assembled therein are only about 77% and 70%, respectively.

[0158] It can be seen from the preparation parameters and test results of the negative electrode materials in Examples 6 to 7 that when the pressure adjusts the relative orientation of the pores and particles in the natural graphite, the pressure P1 is applied along the pore orientation, and the pressure P2 is applied along the particle orientation. If P1 / T1 is too small, the pore orientation will be inclined toward the particle orientation, and the average pore orientation degree of the natural graphite will be too small, resulting in the cycle capacity retention rate and rate retention rate of the natural graphite as a negative electrode material in the lithium battery being lower than 90% and 75%, respectively; if P1 / T1 is too large, the effects of the pressure P1 and the pressure P2 on the natural graphite will be offset, and the pressure adjustment effect will not be obvious. The average pore orientation degree of the natural graphite is too small, resulting in the cycle capacity retention rate and rate retention rate of the natural graphite as a negative electrode material in the lithium battery being lower than 90% and 75%, respectively.

[0159] It can be seen from the preparation parameters and test results of the negative electrode materials in Examples 8 to 9 that when the pressure adjusts the relative orientation of the pores and particles in the natural graphite, the pressure P1 is applied along the pore orientation, and the pressure P2 is applied along the particle orientation. If P2 / T2 is too large, the pore orientation will be inclined toward the particle orientation, and the average pore orientation degree of the natural graphite will be small, resulting in the cycle capacity retention rate and rate retention rate of the natural graphite as a negative electrode material in a lithium battery being lower than 90% and 75%, respectively; if P1 / T1 is too small, the effects of the pressure P1 and the pressure P2 on the natural graphite will be offset, and the pressure adjustment effect will not be obvious. The average pore orientation degree of the natural graphite is small, resulting in the cycle capacity retention rate and rate retention rate of the natural graphite as a negative electrode material in a lithium battery being lower than 90% and 75%, respectively.

[0160] It can be seen from the preparation parameters and test results of the negative electrode materials in Examples 10 to 11 that when the average pore orientation of natural graphite is lower than 5°, the electrolyte wetting effect and lithium ion transmission capacity of natural graphite as a negative electrode material in a lithium battery are weakened, thereby causing the cycle capacity retention rate and rate retention rate of natural graphite to be greatly reduced, wherein the cycle capacity retention rate is reduced from about 94% to 81.2%, and the rate retention rate is reduced from about 80% to 73.6%; when the average pore orientation of natural graphite is higher than 40°, the structural stability deviation of natural graphite as a negative electrode material on the negative electrode sheet causes a significant reduction in the cycle capacity retention rate and rate retention rate of natural graphite, wherein the cycle capacity retention rate is reduced from about 94% to 85.7%, and the rate retention rate is reduced from about 80% to 70.8%.

[0161] It can be seen that the natural graphite adjusted by the preparation method of the present invention, when the average pore orientation degree is 5° to 40°, can be used as a negative electrode material to have both high structural stability and lithium ion transmission performance, so that the negative electrode material has a higher cycle capacity retention rate and rate retention rate in the lithium battery, and can improve the cycle performance and fast charging performance of the assembled battery.

[0162] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A negative electrode material, characterized in that: include: Natural graphite, wherein the particles of the natural graphite have pores; The average pore orientation of the natural graphite is 5° to 40°, and the pore orientation is the angle between the pore orientation and the particle orientation in the natural graphite particles.

2. The negative electrode material according to claim 1, characterized in that: The negative electrode material comprises a core body and a coating layer, wherein the core body comprises the natural graphite, and the coating layer comprises amorphous carbon.

3. The negative electrode material according to claim 1, characterized in that: The average particle size of the natural graphite particles is 5 to 20 μm.

4. A method for preparing the negative electrode material according to any one of claims 1 to 3, characterized in that: include: Performing shaping treatment on natural graphite raw materials to obtain a first graphite precursor; Applying a pressure P1 to the first graphite precursor along a first direction for a holding time T1, maintaining the pressure P1 unchanged and applying a pressure P2 to the first graphite precursor along a second direction for a holding time T2, thereby obtaining a second graphite precursor; The second graphite precursor is mixed with a coating agent to perform carbon coating treatment to obtain a negative electrode material; The first direction is perpendicular to the second direction, and the pressure P1 is less than the pressure P2.

5. The method for preparing the negative electrode material according to claim 4, characterized in that: The natural graphite raw material includes at least one of flake graphite and microcrystalline graphite.

6. The method for preparing the negative electrode material according to claim 4, characterized in that: The shaping process of the natural graphite raw material comprises: The natural graphite raw material is crushed, spheroidized and classified to obtain the first graphite precursor; wherein the average particle size of the first graphite precursor is 10 to 20 μm.

7. The method for preparing the negative electrode material according to claim 4, characterized in that: The pressure of the pressure P1 is 5-10 MPa, the time T1 is 0.5-1 hour, the pressure of the pressure P2 is 10-20 MPa, and the time T2 is 1-2 hours.

8. The method for preparing the negative electrode material according to claim 4, characterized in that: The coating agent includes at least one of coal tar, petroleum tar, medium-temperature tar, phenolic resin and ethylene tar.

9. The method for preparing the negative electrode material according to claim 4, characterized in that: The mass ratio of the second graphite precursor to the coating agent is (5-20):1, and the carbon coating treatment temperature of the second graphite precursor and the coating agent is 1000-1200°C.

10. A negative electrode plate, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer comprises the negative electrode material according to any one of claims 1 to 3, or the negative electrode material prepared by the preparation method according to any one of claims 4 to 9.

11. The negative electrode plate according to claim 1, characterized in that: The average pore orientation degree of the pores in the negative electrode material relative to the plane of the negative electrode current collector is 5° to 40°.

12. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a separator, an electrolyte and the negative electrode sheet according to claim 10 or 11.

Citation Information

Cited By

  • Negative electrode material and battery

    WO2026098355A1